Absence of gargling affects topical adverse symptoms caused by inhaled corticosteroids in females. (March 2014) - Kajiwara, Ayami; Kita, Ayana; Saruwatari, Junji; Morita, Kazunori; Oniki, Kentaro; Yamamura, Masato; Murase, Motoji; Koda, Haruo; Hirota, Seisuke; Ishizuka, Tadao; Nakagawa, Kazuko
Abstract Objective: Topical adverse events caused by inhaled corticosteroids (ICS) are suspected to be more common in females. Although gargling or mouth washing after inhalation is recommended as the gold standard for preventing adverse events due to ICS, the preventive effects of this method have not been confirmed in real-world studies. This study aimed to examine the association between gargling or mouth washing and the incidence of topical adverse symptoms in males and females in daily practice. Methods: We analyzed a subpopulation of participants in the Drug Event Monitoring (DEM) project of the Japan Pharmaceutical Association. An anonymous survey was performed in February 2010, to assess the self-perception of topical adverse symptoms during ICS use by conducting interviews of pharmacists using structured questionnaires. Results: A total of 412 males and 480 females were included. The patients used a dry-powder inhaler (DPI) (71.2%), pressurized meter-dose inhaler (pMDI) with (7.5%) or without (16.6%) a spacer or inhalation solution (4.7%) as the delivery device. Topical adverse symptoms occurring after previous prescriptions were reported by 41 (4.6%) subjects. The common symptoms were hoarseness, stomatitis and dry mouth (1.3%, 1.1% and 1.1%, respectively). In the multiple regression model, the presence of symptoms was found to be significantly associated with the absence of gargling or mouth washing after inhalation [adjusted odds ratio (OR): 3.75, 95% confidence interval (95%CI): 1.33–10.59, p = 0.012]. When stratified by gender, the absence of gargling or mouth washing was identified to be a risk factor in females only (OR: 4.32, 95%CI: 1.11–16.87, p = 0.035) and not in males (OR: 3.26, 95%CI: 0.65–16.33, p = 0.151). Furthermore, the association between the absence of gargling or mouth washing and the incidence of topical adverse symptoms was significant in the patients using DPI (OR: 4.85, 95%CI: 1.66–14.14, p = 0.004), but not in those using the other devices. Conclusions: In this study, the absence of gargling or mouth washing after ICS use was associated with topical adverse symptoms, especially in females. To achieve good adherence to treatment and improve the quality of life, female patients with asthma should strictly practice the gargling or mouth washing method.